Phase II randomised controlled trial of a 6-month self-managed community exercise programme for people with Parkinson's disease. - Collett, J; Franssen, M; Meaney, A; Wade, D; Izadi, H; Tims, M; Winward, C; Bogdanovic, M; Farmer, A; Dawes, H (BMJ Publishig Group, 2016)
Background Evidence for longer-term exercise delivery for people with Parkinsons Disease pwP) is deficient. Aim Evaluate safety and adherence to a minimally supported community exercise intervention and estimate effect sizes (ES). Methods Two arm parallel phase II randomised controlled trial with blind assessment. PwP able to walk ≥100meters and with no contraindication to exercise were recruited from the Thames valley, UK and randomised (1:1) to intervention (exercise) or control (handwriting) groups, via a concealed computer-generated list. Groups received a six month, twice weekly program. Exercise was undertaken in community facilities (30minutes aerobic and 30minutes resistance) and handwriting at home, bothwere delivered through workbooks with monthly support visits. Primary outcome was a 2minute walk, with motor symptoms (MDS-UPDRS III), fitness, health and wellbeing measured. Results Between December 2011 and August 2013, n=53 (n=54 analysed) were allocated to exercise and n=52 (n=51 analysed) to handwriting. n=37 adhered to the exercise, most attending ≥1 session/week. Aerobic exercise was performed in 99% of attended sessions and resistance in 95%. Attrition and adverse events(AE) were similar between groups, no Serious AEs (n=2 exercise, n=3 handwriting) were related, exercise group related AEs (n=2) did not discontinue intervention. Largest effects were for motor symptoms (2minute walk ES= 0.20 (95%CI=-0.44:0.45) and MDS-UPDRS III ES=-0.30 (95%CI=0.07:0.54)) in favour of exercise over the 12month follow-up period. Some small effects were observed in fitness and wellbeing measures (ES >0.1). Conclusion pwP exercised safely and the possible long-term benefits observed support substantive evaluation of this community program